Study on the effect of employees' incentives scheme benefits on company's performance - Umikalsom , Yunus (2013)
The paper aims at determining the link between incentive schemes and how it benefits the company performance and provide useful information to management on how best to choose the types of incentive schemes. To achieve this objective, this paper focused on the implementation of employees' incentives scheme at Ansell NP Sdn. Bhd. Two independent variables in incentives schemes were used i.e. the types of incentives scheme and the incentive program term. The findings were that incentive schemes have significant positive relation with company performance at Ansell NP Sdn. Bhd. This paper recommends that management must identify the types of incentive that best motivate the employees based on individual differences and needs; to balance material considerations with non-material reinforcement to maximize job quality and quantity and the management should seek and obtain feedback on how employees perceive incentives.